Knowledge, Attitudes and Practices of Resident Physicians About Antibiotic Resistance - A Comparative Study of Two Departments At A Tertiary Care Hospital - Riaz, Sidra; Nisar, Shazia; Palwa, Abdur Rahim; Saeed, Farrukh; Arshad, Abdul Rehman; Hussain, Mehmood (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the knowledge, attitude, and practices of resident physicians from Department of Surgery with Department of Medicine, about antibiotic resistance (AER) and to determine if better knowledge leads to better attitudes and practices.Study Design: Analytical cross-sectional study.Place and Duration of Study: Departments of Surgery and Medicine, Pak Emirates Military Hospital (PEMH), Rawalpindi, Pakistan, from Jul to Dec 2021.Methodology:  A validated questionnaire exploring knowledge, attitudes and practices (KAP) regarding antibiotic resistance (AR) was administered to 61 resident physicians from Department of Medicine and 55 residents from Department of Surgery, at PEMH, Rawalpindi, Pakistan. All responses were collected and analyzed using Statistical Package for Social Sciences (SPSS) version 25.Results: The average scores of physicians from Department of Medicine were 29.84±3.36, 28± 1.66 and 41.80±3.40 in the knowledge, attitude and practice domains respectively, while they were 26.5± 2.12, 25.42± 2.63 and 37.98±3.45 respectively in the domains of knowledge, attitude and practice for physicians from Department of Surgery. An association was found between the score of knowledge with attitude and practice with Pearson correlation coefficient of 0.31 and 0.33 respectively, however, no correlation was found between year of training and KAP scores.Conclusion: Medicine residents outperformed Surgery residents in antibiotic resistance knowledge (29.84±3.36 vs. 26.5±2.12), attitude (28.00±1.66 vs. 25.42±2.63), and practice (41.80±3.40 vs. 37.98±3.45) scores. Higher knowledge correlated with better attitudes (r=0.31) and practices (r=0.33), independent of training year. Targeted training, especially for surgeons, is recommended to enhance stewardship.